Structural model and algorithm of choice of optimal configurations of the detail, exposed to thermal processing - O. I. Chichko (Литьë и металлургия)
There is offered the model for the optimization of the internal structure and thermal regimes of the object by special functions, formed on the basis of characteristics of the stresses field. There is described the algorithm of choice of the object optimal configuration and presented the functions, illustrating the application of the method to calculation of the detail, exposed to thermal processing.